Role of bioactive lipids in obesity - Salsinha, Ana Sofia (2022)
Obesity continues to be one of the major global challenges in the present century and its incidence nearly tripled between 1975 and 2016. It is estimated that obesity rates are going to increase further by 2030. The available drugs for obesity have not achieved the required level of clinical effectiveness and have been associated with severe health side effects. Diet has been widely recognized as playing a central role in such disorder. Although high-fat diets are often blamed for increased obesity rates, fats are diverse and respond differently in vivo. Saturated fatty acids bind to toll-like receptor 4 (TLR 4) triggering inflammatory processes in the brain, adipose tissue, and liver. Besides, saturated fatty acids are responsible for increased lipid storage in adipose tissue leading to an accumulation of lipids in adipocytes. In contrast, medium-chain fatty acids, monounsaturated and polyunsaturated fatty acids are related to body weight reduction and a protective potential of both peripheral tissues and brain, in part related to their anti-inflammatory capability.